Pengaruh Promosi, Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Produk Bear Brand di Kota Batam - Widiyanti Oktavira; Sunargo (eCo-Buss, 2023)
The growth in fresh milk production in Indonesia has fluctuated in terms of demand for fresh milk every year, but in 2020 to 2021 the demand for fresh milk will increase this is because there is a tendency for the Indonesian people to consume more Bear Brand milk in Indonesia in accordance with the growth in cases Covid-19 that year. However, since the disappearance of the Covid-19 virus in Indonesia, Bear Brand sales have decreased, this is due to the lack of promotion provided, the quality of the products that are not innovative, and the brand image that has not been fully remembered by all groups. The purpose of this study is to find out how promotion, product quality and brand image can influence purchasing decisions on Bear Brand products in Batam City. This research uses quantitative with descriptive. The population used is a buyer or who consumes Bear Brand milk products in Batam City, using the lambeshow formula with the results of 100 respondents. The analysis tools include descriptive statistical tests, data quality tests, classical assumption tests, influence tests and hypothesis testing. The results of the study can show that promotion, product quality and brand image can have a partial or simultaneous positive and significant influence on purchasing decisions on Bear Brand products in Batam City.